Acaricide Resistance in Rhipicephalus sanguineus Infested Dogs in Agartala, Tripura - Pratik Bhowmik; Saidul Islam; De, Ankan; Behera, Debasish; Debbarma, Apurba; Datta, Sukanta (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Development of acaricide resistance in tick population is a major concern in livestock as well as pet animals. Reduced responsiveness has been observed against commonly used acaricides in tick population infesting dogs in the Agartala city which is the capital city of Tripura state of North-eastern part of India. Therefore, the present study was designed to investigate the status of resistance in Rhipicephalus sanguineus ticks of dogs against commonly used acaricide drugs in Agartala city. Two acaricidal compound viz. Deltamethrin and Fipronil were chosen for acaricidal resistance study using two bioassays i.e. Adult Immersion Test (AIT) and Larval Packet Test (LPT). AIT study in respect of deltamethrin revealed the lowest (33.33%±0.002) and highest mortality (86.66%±0.002) of adult ticks at 25 ppm and 200 ppm, respectively. Similarly, lowest (53.33%±0.003) and highest mortality (93.33%±0.001) was recorded at 25 ppm and 100 ppm, respectively in case of fipronil. Whereas, in LPT study, lowest mortality (40.16±0.45%) of R. sanguineus larvae was recorded at 25 ppm of deltamethrin with highest mortality (87.16%±0.12) at 200 ppm. For fipronil, lowest (50.33%±0.52) and highest mortality (99.66%±0.17) was recorded at 25 ppm and at 100 ppm, respectively. The study revealed that both the acaricides produced lower mortality of ticks at their market recommended doses. However, fipronil was found to be more effective than that of deltamethrin. The observed resistance warrants immediate measures to prevent further development of acaricide resistance in the tick population in dogs in the study area.